Thermal and mineralogical performance of serpentinized dunites of Moa-Baracoa region under temperatures up to 1 600 ºC - José Alberto Pons-Herrera; María Caridad Ramírez-Pérez; Rafael Quintana-Puchol; Andrés Salazar-Moreno; Eduardo Montero-Gil; Arisbel Álvarez-Ortiz (Minería y Geología, 2019)
The purpose of this study is to determine the phase transformation and thermal performance of the serpentinized dunites of Moa-Baracoa region subjected to temperatures between 1 200 ° C and 1 600 ° C. To fulfill this purpose X-ray diffraction analysis and thermal analysis (gravimetric and differential) were carried out. Heating the dunites at such temperatures produced a stabilization of the forsterite and periclase phases, which gives important refractory properties to this material which support using this raw material in the metallurgical foundry processes.